Ibrexafungerp: A Novel Oral Triterpenoid Antifungal in Development for the Treatment of Candida auris Infections - Mahmoud Ghannoum; Maiken Cavling Arendrup; Vishnu P. Chaturvedi; Shawn R. Lockhart; Thomas S. McCormick; Sudha Chaturvedi; Elizabeth L. Berkow; Deven Juneja; Bansidhar Tarai; Nkechi Azie; David Angulo; Thomas J. Walsh (MDPI AG, 2020)
Candida auris is an emerging multidrug-resistant fungal pathogen reported worldwide. Infections due to C. auris are usually nosocomial and associated with high rates of fluconazole resistance and mortality. Echinocandins are utilized as the first-line treatment. However, echinocandins are only available intravenously and are associated with increasingly higher rates of resistance by C. auris. Thus, a need exists for novel treatments that demonstrate potent activity against C. auris. Ibrexafungerp is a first-in-class triterpenoid antifungal agent. Similar to echinocandins, ibrexafungerp inhibits (1→3)-β-D-glucan synthase, a key component of the fungal cell wall, resulting in fungicidal activity against Candida spp. Ibrexafungerp demonstrates broad in vitro activity against various Candida spp. including C. auris and C. auris isolates with fks mutations. Minimum inhibitory concentration (MIC50 and MIC90) values in >400 C. auris isolates were 0.5 μg/mL and 1.0 μg/mL, respectively. Clinical results were reported for two patients with invasive candidiasis or candidemia due to C. auris treated during the CARES (Candidiasis Caused by Candida Auris) trial, an ongoing open-label study. These patients experienced a complete response after treatment with ibrexafungerp. Thus, ibrexafungerp represents a promising new antifungal agent for treating C. auris infections.